Gamification in mathematics education: a bibliometric analysis - Supriyadi, Edi; Dahlan, Jarnawi Afgani; Juandi, Dadang; Sugiarni, Rani; Fauzi, Ahmad Lutfi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The aim of this research was to identify patterns in the authors' use of keywords from research publications on gamification in mathematics learning; this would allow us to gauge the productivity and influence of this field of study. For the purpose of doing bibliometric analysis, data from Scopus ranging from 2017 to 2022 was utilized. Included in this investigation were forty-two research articles over the full time period, making the total number of documents included in this study n = 42. Following the execution of the search procedure, the data were taken from Scopus utilizing the.csv file format, and afterwards, they were imported into a spreadsheet utilizing Microsoft Excel. The date for the gathering of data as well as the analysis is the 18th of August in 2022. The SciVal system (https://www.scival.com/) was utilized as a research tool for the goal of analyzing bibliographic indicators. A bibliometric analysis of our publications in gamification in mathematics learning research allows us to conclude that the number of publications is increasing every year. Although the publication activity of indexed scientists in Scopus is still low in this study. Study on gamification in mathematics education is the most researched topic in the social sciences. Dureva is the author of the most impactful publications on gamification of mathematics education. Both Bina Nusantara University in Indonesia and South-West University Neofit Rilski in Bulgaria are universities that have produced two scholarly documents each, making them the only two universities in the world to share this output. The journal Advances in Intelligent Systems and Computing has the most scholarly output and is the most visited on its journal website. The finding that this research can give a basis for selecting the research that will be carried out by raising the topic of gamification in mathematics education is the consequence that was derived from this research. Because certain keywords in the field of research on the gamification of mathematics education are always subject to change. In addition, this research on bibliometric analysis can be utilized for systematic literature research and meta-analysis linked to gamification in mathematics education, and it can also be used to improve research that has already been conducted.